Estimation of Fuel Economy Improvement in Gasoline Vehicle Using Cylinder Deactivation - Nankyu Lee (Energies, 2018)
Cylinder deactivation is a fuel economy improvement technology that has attracted particular attention recently. The currently produced cylinder deactivation engines utilize fixed-type cylinder deactivation in which only a fixed number of cylinders are deactivated. As fixed-type cylinder deactivation has some shortcomings, variable-type cylinder deactivation with no limit on the number of deactivated cylinders is under research. For variable-type cylinder deactivation, control is more complicated and production cost is higher than fixed-type cylinder deactivation. Therefore, it is necessary to select the cylinder deactivation control method considering both advantages and disadvantages of the two control methods. In this study, a fuel economy prediction simulation model was created using the measurement data of various vehicles with engine displacements of 1.0⁻5.0 L. The fuel economy improvement of fixed-type cylinder deactivation was compared with that of variable-type cylinder deactivation using the created simulation. As a result of examining the fuel economy improvement of the test vehicle in the FTP-75 driving cycle, the improvement was 2.2⁻10.0% for fixed-type cylinder deactivation and 2.2⁻12.8% for variable-type cylinder deactivation. Furthermore, the effect of the engine load on fuel economy improvement under cylinder deactivation and the effect of changes in engine control were examined via a simulation.